Effect of turmeric extract on glutathione levels in diclofenac-induced oxidative stress in rats - Cynthia Benedikta Jumba; Anita Lidesna Shinta Amat; Prisca Deviani Pakan; Desi Indria Rini (Acta Biochimica Indonesiana, 2025)
Background: Glutathione (GSH), the primary endogenous antioxidant, protects cells against oxidative stress. Diclofenac sodium, a commonly prescribed nonsteroidal anti-inflammatory drug (NSAID), depletes GSH through hepatic metabolic byproducts, causing oxidative damage. Objective: To evaluate the protective effect of turmeric extract (Curcuma longa L.) on glutathione levels in rats subjected to diclofenac-induced oxidative stress. Methods: Twenty-eight male Wistar rats were randomly divided into four groups (n=7): normal control, negative control (diclofenac sodium 10 mg/kg body weight [BW]), and two treatment groups receiving turmeric extract (100 mg/kg BW or 200 mg/kg BW) following diclofenac induction. Diclofenac was administered for 7 days; turmeric extract was given orally for 14 days. Cardiac blood glutathione levels were measured spectrophotometrically. Results: Turmeric extract significantly increased glutathione levels in diclofenac-induced rats compared to negative controls (p<0.05). The 200 mg/kg BW dose produced superior protection, elevating GSH levels significantly above all groups (p<0.001), demonstrating a dose-dependent antioxidant effect. Conclusion: Turmeric extract demonstrates significant dose-dependent antioxidant activity against diclofenac-induced oxidative stress, with the 200 mg/kg BW dose achieving superior GSH elevation (p < 0.001), suggesting potential as a protective agent against NSAID-induced oxidative damage.